HELLP syndrome against the background of glomerulonephritis: Clinical casereport - L. Lebid; L. Snisar; L. Liksunova (Ukrainian Journal of Nephrology and Dialysis, 2019)
HELLP syndrome (hemolysis, elevated liver enzymes, and low platelets) is a severe and rapidly progressing condition that requires distinct diagnostic considerations. The clinical presentation varied within all of the classes, and the only objective means of diagnosis and evaluation of progression of the condition are laboratory tests. HELLP syndrome may result in severe morbidity and mortality to both the mother and fetus.In this case, we reported that a patient with chronic glomerulonephritis was diagnosed with HELLP syndrome.The case was collected in Institute of Nephrology of the National Academy of Medical Sciences, Kyiv, Ukraine.